Cloning, purification, and functional characterization of Carocin S2, a ribonuclease bacteriocin produced by Pectobacterium carotovorum - Chan, Yung-Chieh; Wu, Jian-Li; Wu, Huang-Pin; Tzeng, Kuo-Ching; Chuang, Duen-Yau (BMC microbiology, 2011)
Most isolates of Pectobacterium carotovorum subsp. carotovorum (Pcc) produce bacteriocins. In this study, we have determined that Pcc strain F-rif-18 has a chromosomal gene encoding the low-molecular-weight bacteriocin, Carocin S2, and that this bacteriocin inhibits the growth of a closely related strain. Carocin S2 is inducible by ultraviolet radiation but not by mutagenic agents such as mitomycin C. A carocin S2-defective mutant, TF1-2, was obtained by Tn5 insertional mutagenesis using F-rif-18. A 5706-bp DNA fragment was detected by Southern blotting, selected from a genomic DNA library, and cloned to the vector, pMS2KI. Two adjacent complete open reading frames within pMS2KI were sequenced, characterized, and identified as caroS2K and caroS2I, which respectively encode the killing protein and immunity protein. Notably, carocin S2 could be expressed not only in the mutant TF1-2 but also in Escherichia coli DH5α after entry of the plasmid pMS2KI. Furthermore, the C-terminal domain of CaroS2K was homologous to the nuclease domains of colicin D and klebicin D. Moreover, SDS-PAGE analysis showed that the relative mass of CaroS2K was 85 kDa and that of CaroS2I was 10 kDa. This study shown that another nuclease type of bacteriocin was found in Pectobacterium carotovorum. This new type of bacteriocin, Carocin S2, has the ribonuclease activity of CaroS2K and the immunity protein activity of CaroS2I.